Sulfur hexafluoride plasma surface modification of Gly-Ala and Ala-Gly as Bombyx mori silk model compounds: Mechanism investigations - Sangprasert W. (2014)
Low-pressure plasma has been used to improve the hydrophobicity of Thai silk. In this study, Glycine-Alanine (GA) and Alanine-Glycine (AG) were chosen to represent model compounds of Bombyx mori silk. Single crystals of the simplified model compounds were characterized by polarizing microscopy and X-ray diffraction. The space groups of P212121 and P21 were found for AG and GA, respectively. The initial structures for calculation were obtained from the experimental crystal structures. Density functional theory at the BHandHLYP levels was used to investigate possible mechanisms of fluorine radicals reacting with AG and GA in the SF6 plasma treatment. The results indicate that hydrogen atoms of silk model compounds were most likely to be abstracted from the alanine residue. © 2009 Elsevier B.V. All rights reserved.